Exploitation status and stock assessment of daisy parrotfish (Chlorurus sordidus) in Karimunjawa Marine National Park, Central Java, Indonesia - DIAN WIJAYANTO; ALHADI BUSTAMAM; YANDRA ARKERMAN; KHAIRUL AMRI; TIRTADANU TIRTADANU; GATHOT WINARSO; IRMAN HERMADI; SARI INTAN KAILAKU; FAIK KUROHMAN; MUHAMMAD REYHAN PUTRANTO; DITA JUNI KURNIA (Society for Indonesian Biodiversity, 2025)
Abstract. Wijayanto D, Bustamam A, Arkerman Y, Amri K, Tirtadanu, Winarso G, Hermadi I, Kailaku SI, Kurohman F, Putranto MR, Kurnia DJ. 2025. Exploitation status and stock assessment of daisy parrotfish (Chlorurus sordidus) in Karimunjawa Marine National Park, Central Java, Indonesia. Biodiversitas 26: 4831-4837. Daisy parrotfish (Chlorurus sordidus) play a crucial ecological role in maintaining coral reef health and resilience by grazing on algae, which prevents algal overgrowth and promotes coral recruitment. This study evaluated the exploitation status of C. sordidus in the Karimunjawa Marine Protected Area, Central Java, Indonesia, using biological indicators, including length at first capture (Lc??%), growth parameters, and mortality rates. Field sampling was conducted from March 2024 to February 2025, involving fisher interviews and morphometric measurements of 1,032 individuals. Results showed a Lc??% of 24.8 cm and an asymptotic length (L?) of 51 cm, exceeding the size of first maturity but below the sex-change size range, potentially affecting reproductive dynamics. Further analysis revealed total mortality (Z) of 4.31 year-¹, with fishing mortality (F = 2.33) higher than natural mortality (M = 1.20), reflecting intensive fishing pressure on the stock. The exploitation rate (E: 0.54) indicates that the species is currently overexploited, which may reduce herbivory functions, weaken coral reef resilience, and threaten long-term fishery benefits. These findings highlight the urgent need for effective management measures, including minimum size limits, seasonal fishing restrictions, and community-based compliance, to ensure population sustainability. Continuous monitoring and further research on reproductive biology and critical habitats, particularly nursery grounds and spawning aggregations, are essential for informed conservation strategies, ensuring not only population sustainability but also the maintenance of ecosystem services that support local livelihoods and marine ecotourism in Karimunjawa.